The Effect of Stock Turnover and Auditor Selection on Premiums Paid in Acquisition Transactions : Evidence From Indonesia - Hanandewa . (Indonesian Management and Accounting Research, 2012)
This study focus on the determinants of premiums paid in acquisition transaction of public companies. In this type of transaction, the acquisition price is usually priced at premium above the exchange price. Motivated by contradictory findings in previous literatures, two hypotheses are proposed to explain the phenomenon. First, is that there is a positive relationship between premiums paid and target's stock liquidity. And second, is that there is a positive relationship between premiums paid and information quality. These hypotheses are tested using historical data of such acquisition transactions that comprise at least 20° 0 of target's equity and that have been occurred in the Indonesian stock exchange during 2000-2010. The findings suggest that stock turnover, as a proxy for stock liquidity, and auditor selection, as a proxy for information quality; do have significant impact on the premiums paid, which confirm previous studies. However, unlike a priori expectation, the relationship between stock liquidity and the premiums paid is negative. We argue that analysts coverage that can act like a minority shareholders protection help to explain this negative relation between stock liquidity and the premiums paid.